James Cook the voyages - Frame, William 1972-; Walker, Laura 1986- (McGill-Queen's University Press, 2018)
"The twenty-fifth of August 2018 marks the 250th anniversary of the departure of the Endeavour from Plymouth, England, and the first of three voyages by James Cook that would nearly complete the map of the world. Interweaving accounts of scientific discovery with the personal stories of the voyages' key participants, William Frame and Laura Walker explore the charting of the Pacific and the natural world, the first encounters and exchange between Western and indigenous cultures, and the representation of the voyages in art. The illustrations, many of which have never before been published, include drawings by all the artists employed on the voyages, including Alexander Buchan, Sidney Parkinson, William Hodges, and John Webber. It also includes the only surviving paintings by Tupaia, a Polynesian high priest and navigator who joined the first voyage at Tahiti and sailed with Cook to New Zealand and Australia. A stunningly illustrated object-centred history, James Cook: The Voyages offers a once-in-a-generation opportunity to discover the extensive Captain Cook collection of the British Library, including original maps, artworks, journals, and printed books."--
Keywords: Webber, John -- 1751-1793; Hodges, William -- 1744-1797; Cook, James -- 1728-1779; Parkinson, Sydney -- 1745-1771; Forster, Georg -- 1754-1794; British Library; Geschichte 1768-1780; Kunst; Indigenes Volk; Reisebericht; Sammlung; Entdeckungsreise; Karte; Reisebild; Cook, James / 1728-1779; Cook, James / 1728-1779 / Travel / Pacific Area; SCIENCE / Earth Sciences / Geography; Explorers / Great Britain / Biography; Voyages around the world / History / 18th century; Natural history / History / 18th century; Travel in art; Pacific Area / Discovery and exploration / British; Oceania / Discovery and exploration / British; Biografie